Retroperitoneal Compared to Transperitoneal Approach for Open Abdominal Aortic Aneurysm Repair Is Associated with Reduced Systemic Inflammation and Postoperative Morbidity - Bailey, Damian M.; Rose, George A.; O'Donovan, Daniel; Locker, Dafydd; Appadurai, Ian R.; Davies, Richard G.; Whiston, Richard J.; Bashir, Mohamad; Lewis, Michael H.; Williams, Ian M. (AORTA, 2022)
Background In the United Kingdom, the most common surgical approach for repair of open abdominal aortic aneurysms (AAAs) is transperitoneal (TP). However, retroperitoneal (RP) approach is favored in those with more complex vascular anatomy often requiring a cross-clamp on the aorta superior to the renal arteries. This study compared these approaches in patients matched on all major demographic, comorbid, anatomic, and physiological variables.Methods Fifty-seven patients (TP: n = 24; RP: n = 33) unsuitable for endovascular aneurysm repair underwent preoperative cardiopulmonary exercise testing prior to open AAA repair. The surgical approach undertaken was dictated by individual surgeon preference. Postoperative mortality, complications, and length of hospital stay (LoS) were recorded. Patients were further stratified according to infrarenal (IR) or suprarenal/supraceliac (SR/SC) surgical clamping. Systemic inflammation (C-reactive protein) and renal function (serum creatinine and estimated glomerular filtration rate) were recorded.Results Twenty-three (96%) of TP patients only required an IR clamp compared with 12 (36%) in the RP group. Postoperative systemic inflammation was lower in RP patients (p = 0.002 vs. TP) and fewer reported pulmonary/gastrointestinal complications whereas renal impairment was more marked in those receiving SR/SC clamps (p < 0.001 vs. IR clamp). RP patients were defined by lower LoS (p = 0.001), while mid-/long-term mortality was low/comparable with TP, resulting in considerable cost savings.Conclusion Despite the demands of more complicated vascular anatomy, the clinical and economic benefits highlighted by these findings justify the more routine adoption of the RP approach for complex AAA repair.
Keywords: abdominal aortic aneurysm repair; retroperitoneal; transperitoneal; cardiorespiratory fitness; inflammation